"Why not together?" How different roles regulate inclination to participate in a peer-to-peer access-based market - Teixeira, Otávio Ferreira Borges (2016)
This study is about markets (supply and demand) based on sharing, a type of exchange that is going through an innovation process. In an access-based market, people diminish the traditional way of buying and selling the ownership of products and start (or increase) to buy and sell the access to these goods. Despite the well-known practice of sharing things, the internet not only changed this dynamic but also multiplied its adoption. Surprisingly, the relationship between people’s possible roles and their shared goods has not been explored in several academic perspectives. This article addresses part of these gaps, hypothesizing that people still carry on feelings of gains and losses when they are sharing as is commonly observed in situations in which they are buying or selling, enlarging previous researches. More than that, this study is attentive to the roles of people (consumer x provider) and intensity of sharing on willingness to share, checking the effort that each role makes to change (or not) the intensity of sharing and, mapping the main antecedents that determined the judgments of each role when about to share. Results suggest that the higher (or lower) the intensity of sharing, the higher is the providers’ (or consumers’) propensity to share; this because the psychological ownership manifests divergently between roles: providers value their assets more and the control over them, while consumers value their money and the privacy acquired with it. In this realm, five groups of antecedents represent 80% of all reasons for whether or not people engage in sharing.